2014
DOI: 10.4244/eijy14m08_03
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frailty on short- and long-term morbidity and mortality after transcatheter aortic valve implantation: risk assessment by Katz Index of activities of daily living

Abstract: Frailty status measured by the Katz Index represents a powerful predictor of adverse early and late outcome after TAVI, whereas commonly used risk scores lack calibration and discrimination in a TAVI-specific patient cohort. Therefore, we propose the incorporation of this simple and reproducible measure into pre-TAVI risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 27 publications
5
91
1
8
Order By: Relevance
“…Suggested criteria for the diagnosis of frailty included 5 min walking time, grip strength, BMI <20 kg/m 2 and/or weight loss of 5 kg/year, serum albumin<3.5 g/dL, and cognitive impairment or dementia. Frailty was hence found to be a strong predictor of mortality and adverse outcomes following cardiac surgery and TAVI [26][27][28]. In this study, the authors found frailty to be present in 21.5% of obese patients vs 44.7% of patients with normal weight (p < 0.001).…”
Section: Discussionsupporting
confidence: 50%
“…Suggested criteria for the diagnosis of frailty included 5 min walking time, grip strength, BMI <20 kg/m 2 and/or weight loss of 5 kg/year, serum albumin<3.5 g/dL, and cognitive impairment or dementia. Frailty was hence found to be a strong predictor of mortality and adverse outcomes following cardiac surgery and TAVI [26][27][28]. In this study, the authors found frailty to be present in 21.5% of obese patients vs 44.7% of patients with normal weight (p < 0.001).…”
Section: Discussionsupporting
confidence: 50%
“…Finally, 2 other small studies of 100 to 200 patients also found higher mortality in frail patients after adjustment. 21,22 Our study demonstrates the average gait speed observed in a large TAVR cohort and confirms the utility of gait speed as a single marker of frailty. The slowest walkers were older, more often female, and obese, with a higher prevalence of previous stroke, chronic lung disease, and heart failure.…”
Section: Discussionmentioning
confidence: 56%
“…La evaluación de la fragilidad no debe partir de un enfoque subjetivo, como una evaluación rápida y superficial, sino de la combinación de una serie de determinaciones objetivas. Actualmente están disponibles varias herramientas para evaluar la fragilidad 23,26,27 .…”
Section: Consideraciones Especiales Con Pacientes Ancianosunclassified